Research Trends from The Scopus Database Using Keyword Water Hyacinth and Ecosystem: A Bibliometric Literature Review - Nandiyanto, Asep Bayu Dani; Fiandini, Meli; Al Husaeni, Dwi Novia (Universitas Pendidikan Indonesia (UPI), 2024)
The problem of water hyacinth (Eichhornia crassipes) invading aquatic biota ecosystems is a hot issue that is currently being discussed throughout the world. Due to the many solutions proposed in academia for their management, mitigation, and utilization, it is necessary to investigate through systematic research. Based on this, this study aims to present research developments on the topic of water hyacinths and ecosystems using bibliometric analysis. In this research, a total of 227 articles from 2000 to 2023 years regarding the keywords “water hyacinth” AND “ecosystem” were taken from Scopus which was used for further analysis. To accomplish the bibliometric analysis, the software programs VOSviewer was used. Based on the findings, it shows that the number of article publications over the last 23 years (2000-2023) has experienced fluctuating changes which are divided into three periods. The pioneering and growth periods were identified in 2000-2008 and 2009-2015. Meanwhile, the acceleration period will occur in 2016-2023. According to the results of data visualization, it was found that there were 4 clusters. The keyword